Magnetic resonance imaging (MRI) features of cataracts in pediatric and young adult patients - Barakat, Elie (Quant Imaging Med Surg, 2020)
BACKGROUND: The goal of this study is to systematically evaluate the magnetic resonance imaging (MRI) signal characteristics and size of cataracts that may be encountered in pediatric and young adult patients. METHODS: A retrospective analysis of the MRI features with cataracts in a series of cases, including characterization of signal intensity on T2-weighted and T1-weighted sequences, as well as measuring the thickness of the lens. RESULTS: Among nine cataracts in seven patients, three lenses were thickened and hyperintense on T2-weighted sequences, presumably related to osmotic effects. The rest of the lenses were either normal in size and signal characteristics, such as in the cases of neurofibromatosis type 2 or small in cases of microphthalmos, with signal characteristics related to calcifications. CONCLUSIONS: There are several different types of cataracts that can occur in pediatric and young adult patients, which may or may not be conspicuous on MRI. The findings in this study can serve as a guide for what abnormalities of the lens may be encountered on MRI.